Protein source and quality for skeletal muscle anabolism in young and older adults: A systematic review and meta-analysis - Morgan, P. T.; Harris, D. O.; Marshall, R. N.; Quinlan, J. I.; Edwards, S. J.; Allen, S. L.; Breen, L. (The Journal of Nutrition, 2021)
Background: There is much debate regarding the source/quality of dietary proteins in supporting indices of skeletal muscle anabolism. Objective: We performed a systematic review and meta-analysis to determine the effect of protein source/quality on acute muscle protein synthesis (MPS) and changes in lean body mass (LBM) and strength, when combined with resistance exercise (RE). Methods: A systematic search of the literature was conducted to identify studies that compared the effects of =2 dose-matched, predominantly isolated protein sources of varying "quality." Three separate models were employed as follows: 1) protein feeding alone on MPS, 2) protein feeding combined with a bout of RE on MPS, and 3) protein feeding combined with longer-term resistance exercise training (RET) on LBM and strength. Further subgroup analyses were performed to compare the effects of protein source/quality between young and older adults. A total of 27 studies in young (18-35 y) and older (=60 y) adults were included. Results: Analysis revealed an effect favoring higher-quality protein for postprandial MPS at rest [mean difference (MD): 0.014%/h; 95% CI: 0.006, 0.021; P < 0.001] and following RE (MD: 0.022%/h; 95% CI: 0.014, 0.030; P < 0.00001) in young (model 1: 0.016%/h; 95% CI: -0.004, 0.036; P = 0.12; model 2: 0.030%/h; 95% CI: 0.015, 0.045; P < 0.0001) and older (model 1: 0.012%/h; 95% CI: 0.006, 0.018; P < 0.001; model 2: 0.014%/h; 95% CI: 0.007, 0.021; P < 0.001) adults. However, although higher protein quality was associated with superior strength gains with RET [standardized mean difference (SMD): 0.24 kg; 95% CI: 0.02, 0.45; P = 0.03)], no effect was observed on changes to LBM (SMD: 0.05 kg; 95% CI: -0.16, 0.25; P = 0.65). Conclusions: The current review suggests that protein quality may provide a small but significant impact on indices of muscle protein anabolism in young and older adults. However, further research is warranted to elucidate the importance of protein source/quality on musculoskeletal aging, particularly in situations of low protein intake.